Trends and determinants of epinephrine prescriptions: a proxy of anaphylaxis epidemiology?. Issue 6 (27th December 2022) - Costa, Enrico; Tanno, Luciana Kase; Salazzari, Damiano; Tedeschi, Federico; Andretta, Margherita; Caminati, Marco
Abstract : Purpose of review: Epinephrine autoinjectors (EAIs) are recommended to all patients previously experiencing anaphylaxis reaction in order to prevent further reactions and fatalities. Under that perspective, EAI prescription could be considered as a proxy of anaphylaxis epidemiology. Nevertheless EAI prescription rates are still unacceptably low. Recent findings: The review focuses on potential determinants, in addition to clinical indications, which might impact EAI prescription rates by exploring the scientific literature published within the past 18 months, wherever available. Although some controversial results, age, sex, ethnicity, geographical setting and socioeconomic conditions might influence both physician prescription behaviour and EAIs' accessibility from the patient's side, which hampers the accuracy of EAI prescription as a proxy of anaphylaxis. Low EAI prescription and refill rates have been recorded even in the absence of significant socioeconomic barriers, suggesting that economical limitations only partially account for the issue, and cultural restrictions have also to be considered and addressed. Summary: In addition to providing the same opportunities in terms of EAI availability in all countries worldwide, implementing the resources for anaphylaxis management in terms of practical knowledge, education, and allergy specialist networks is an urgent need, even in the absence of socioeconomic barriers.